Lock-in and the transition to hydrogen cars. When should governments intervene? - Mads Greaker; Tom-Reiel Heggedal (Statistics Norway, Research Department, 2007)
The density of fuel filling stations influences consumers' utility of private car transport. Thus, to the extent that different modes of private transport require different fuels, there may exist a network externality in the consumption of private transport. We investigate this in a formal model of the market for private transport. In the model there are two competing technologies; today's internal combustion engine based on fossil fuels, and tomorrow's hydrogen car. Due to the network externality there may exist several market equilibriums, of which one is likely to Pareto dominate the other(s). Thus, a lock-in situation is possible. On the other hand, if either the costs of establishing hydrogen filling stations is too high or the hydrogen car technology is still in its infancy, the only equilibrium is the current internal combustion engine equilibrium. Hence, apart from internalizing the environmental externality on gasoline cars, the government has no reasons to intervene before the technology is ripe. And even then, governments should take great care so as not to create a situation of excess momentum.
Keywords: L11; L15; L62; Q42; 330; Lock-in; Path dependency; Hydrogen economy; Climate change policy